1989
DOI: 10.1111/j.1532-5415.1989.tb02267.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Hypertension in an Ambulatory Elderly Population

Abstract: Investigations of the natural history of blood pressure have generally evaluated mean systolic and diastolic pressure changes. While information, this information is not directly applicable to clinical practice settings, in which patients are usually classified as normotensive or hypertensive. We measured the actual incidence of hypertension, using two different definitions, in an ambulatory elderly population of 2,584 individuals over an 8-year period. Using the less stringent blood pressure definition (systo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…First, if there actually are unrecognized hypertensives we would not expect them to be differently distributed within the two groups. Moreover, the 56% prevalence of hypertension found in the study population is very close to the 66% reported when investigating an ambulatory elderly population [178] , considering that in our case some of the hypertensives were lost due to exclusion criteria; this seems to suggests that unrecognized hypertension is not a major problem in our study, consistently with the fact that it enrolled older adults accessing secondary care who are likely to have been screened for high BP by their GPs. Second, hypertensives treated with a lesser number of medications are not necessarily uncontrolled hypertensives; on the contrary they may be subjects whose hypertension is more amenable to therapy.…”
Section: Discussionsupporting
confidence: 84%
“…First, if there actually are unrecognized hypertensives we would not expect them to be differently distributed within the two groups. Moreover, the 56% prevalence of hypertension found in the study population is very close to the 66% reported when investigating an ambulatory elderly population [178] , considering that in our case some of the hypertensives were lost due to exclusion criteria; this seems to suggests that unrecognized hypertension is not a major problem in our study, consistently with the fact that it enrolled older adults accessing secondary care who are likely to have been screened for high BP by their GPs. Second, hypertensives treated with a lesser number of medications are not necessarily uncontrolled hypertensives; on the contrary they may be subjects whose hypertension is more amenable to therapy.…”
Section: Discussionsupporting
confidence: 84%